2009
DOI: 10.1038/aps.2009.157
|View full text |Cite
|
Sign up to set email alerts
|

2-Amino-nonyl-6-methoxyl-tetralin muriate inhibits sterol C-14 reductase in the ergosterol biosynthetic pathway

Abstract: Aim: To investigate the action mechanism of a novel chemical structural aminotetralin derivate, 2-Amino-Nonyl-6-Methoxyl-Tetralin Muriate (10b), against Candida albicans (C albicans) in the ergosterol biosynthetic pathway. Methods: Antifungal susceptibility test of 10b was carried out using broth microdilution method, the action mechanism of 10b against C albicans was investigated by GC-MS spectrometry and real-time RT-PCR assay, and cytotoxicity of 10b in vitro was assessed by MTS/ PMS reduction assay. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…In vitro anti-biofilm activity of 10b 10b had been reported to have great antifungal activity [36,37] , but its dramatic anti-biofilm activity was unexpected. CLSM showed that normal C albicans biofilm exhibited a typical three-dimensional structure and composed mainly of true hyphae and pseudohyphae ( Figure 2A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro anti-biofilm activity of 10b 10b had been reported to have great antifungal activity [36,37] , but its dramatic anti-biofilm activity was unexpected. CLSM showed that normal C albicans biofilm exhibited a typical three-dimensional structure and composed mainly of true hyphae and pseudohyphae ( Figure 2A).…”
Section: Resultsmentioning
confidence: 99%
“…10b is a novel chemical structural antifungal agent with high antifungal activity, a broad antifungal spectrum and potentially low toxicity [36,37] . In this study, we found that 10b had strong anti-biofilm activity.…”
Section: Discussionmentioning
confidence: 99%
“…DCA was chosen as an example and applied to the identification of sterols in yeast cells by MALDI-FT ICR MS. Sterols are important components of the yeast membrane and inhibiting the synthesis of or direct interaction with sterols are mechanisms of antifungal agents in clinical use [5][6][7]31]. The mechanism of resistance to azoles is also related to the metabolic pathway of sterols.…”
Section: Application To the Analysis Of Sterols In Yeast Cellsmentioning
confidence: 99%
“…The target compounds were predominantly detected as [M + Na] + using DCA. The metabolic pathway of sterols in fungi has been reported [4,6], and based on the previous research and elemental composition analysis of target ions by high-resolution FT ICR MS, sterols and their isomers were identified by accurate mass measurements. Since FT ICR MS is high-resolution, the exact m/z values of sterols can be measured accurately to determine their elemental compositions.…”
Section: Application To the Analysis Of Sterols In Yeast Cellsmentioning
confidence: 99%
See 1 more Smart Citation